Машина Поста - Успенский Владимир Андреевич (Популярные лекции по математике; Вып. 54, 1988)
Экземпляры: КХ (20090218) / Инвентарный номер: 0280333 / Цена: 0.20 / Сис.шифр: 32.97 / Авт.знак: У 77 / ГРНТИ: 50 / ББК: 32.97